If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -35 = 8 Reorder the terms: -35 + 15x = 8 Solving -35 + 15x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 15x = 8 + 35 Combine like terms: -35 + 35 = 0 0 + 15x = 8 + 35 15x = 8 + 35 Combine like terms: 8 + 35 = 43 15x = 43 Divide each side by '15'. x = 2.866666667 Simplifying x = 2.866666667
| 5x+7=12x-56 | | 32=5x-3 | | -x^4=25-26x^2 | | 15+4a=7a | | -3.8x+1.2=-17.8 | | 35-8=x | | 9x^2-2=o | | n+2=-14-na | | (1+2)+0= | | 3x=5x+70 | | 3-1.5(x+1)=6x-9 | | 63x^3+11x^2=-36x | | 20+1.25n=2.50n | | 121=100+0.3x | | -8x-3+9x=-9x+3 | | 6(b-a)=2(4a-3b) | | 8x+10=6x+90 | | 205+205+205= | | 0=-16x^2+96x+640 | | 4(x+1)-5(3-x)=14x-2(5x-3) | | 7-4(s-3)=23 | | .5x+3x+(2x+4)= | | 5=-16t^2+45t+6 | | 12x-108=-4x+36 | | 3x=2(-3)-18 | | 5u^2=-26u-5 | | 30=8+2(a+2) | | 12x+3=-7x+22 | | 12x+6=5(3x-2) | | 8x+40=-4x-68 | | 3-7x=8-5x | | 12x+3=-7x |